Quality in education : an implementation handbook - Arcaro, Jerome S. (Delray Beach, Florida : St. Lucie Press, 1995)
Although hundreds of school improvement programs have been launched in the United States over the past quarter century, very few of them have been successful.
1. Introduction -- 2. Leadership -- 3. Malcolm Baldrige National Quality Award for Education -- 4. TQM in Education -- 5. Quality -- 6. Examples of Quality Schools -- 7. TQM Implementation Wheel -- 8. Organizing for Quality -- 9. Creating Quality Task Teams -- 10. The Problem-Solving Cycle -- 11. Problem-Solving Tools and Techniques -- 12. Basic Problem-Solving Tools -- 13. Cost of Quality -- 14. Continuous Improvement -- 15. Conclusion.
Includes index.
Keywords: SCHOOL IMPROVEMENTS